Penggunaan Tenaga Kerja Keluarga Petani Peternak Itik pada Pola Usahatani Tanaman Padi Sawah di Kecamatan Air Hangat Kabupaten Kerinci - Fatati Fatati (Fakultas Peternakan Universitas Jambi, 2006)
The research was aimed to find out the labor employment from farmer and duck veterinarian family at farmer working pattern of rice plantation at Air Hangat Regency. The research was held by using survey method. The samples were 3 villages which were taken by purposive sampling method with determined criterion that the villages have main effort at rice plantation as well as feeding ducks as secondary effort. The villages are Koto Majidin Hilir Village, Majidin Mudik Village and Tebat Ijuk Village. While, the respondents were the veterinarian who were chosen by using Simple Random Sampling Technique. The number of respondents is determined proportionally based on the population number of ducks at each village; there were 20 respondents at Majidin Hilir village, 15 respondents at Majidin Mudik village and 10 respondents at Tebat Ijuk village. The total number was 45 respondents. The research period is based on Effective Working time and the labors are counted based on Man Base Labor. Next, the collected data is processed descriptively. The research result showed that the number of family labor was 57,39 persons per plant season, while the family labor who are employed was 50,69 persons per plant season. Thus the rest of family labor was 6,70 persons per plant season.